Additive functions with big graphs - Kulosman, Hamid; Miller, Harry I. (Annales Mathematicae Silesianae, 1992)
In this note we show that there exists a collection containing c additive functions with big graphs such that f(x) ≠ g{x) for every f,g in the collection (f ≠ g) and every x∈Rn\{0}.